The instruments supporting education for sustainable development - Embros, Grzegorz (Studia Ecologiae et Bioethicae, 2010)
The interdisciplinary nature of environmental protection dooms most of the presently applied protection methods to failure. It is particularly vital an issue in present times of an ecological crisis that occurred as an effect of tackling environmental problems solely from a technical point of view. A crucial role in eliminating the effects and causes of the crisis plays the idea of sustainable development. Therefore, it is necessary to carry out proper educational activities for practical realization of its demands what may end the ecological crisis. The author of the paper presents currently applied educational methods and consequences of their application. Simultaneously he points out a necessity of a holistic approach to education for sustainable development that might be guaranteed, among others, by ecophilosophy. He also highlights the potential of information technology in the realization of educational activities for sustainable development.